The Influence of School Environment and Self-Concept on Students' Interest in Learning in Economics Subjects - Ekawarna, Ekawarna; Riyadi, Riyo; Mindaleni, Mindaleni (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2018)
Interest in learning is a desire and willingness accompanied by deliberate attention and activity and ultimately gives rise to a feeling of enjoyment in the subject, in changes in behavior in the form of knowledge, attitudes and skills. Student interest in learning in the Economics subject of class XI IPS students at SMA Negeri 1 Muaro Jambi is considered to be still far from what is expected. One of the contributing factors is that the school environment is less supportive, apart from that the students' self-concept is also still lacking. This research is a type of Ex Post Facto research that examines events that have occurred and determines the causal factors. With a population of 126 people with a sample of 86 people. Data was collected through an instrument questionnaire with a total of 37 school environment items, 27 self-concept items, and 27 items of student interest in learning. The results of the research show that from the answer to the first hypothesis, the influence of the school environment (X1) on interest in learning (Y) has a significant influence, while the answer to the second hypothesis, the influence of self-concept (X2) on students' interest in learning (Y) has a significant influence, Next, to answer the third hypothesis, testing was carried out jointly, namely the influence of the school environment (X1) and self-concept (X2) on interest in learning (Y). There was a significant influence on the value (Fcount = 174.052>Ftable = 3.11) and R square of 0.807 or 80.7%.